THE NATURE OF THE RELATION BETWEEN SULTAN AL-ZAHIR BAIBARS AND BERKE KHAN - Al Asfour, Dr Soud (Journal of Al-Tamaddun, 2019)
Relation between any two rulers is usually determined by common interests, which may or may not last for long. Those common interests may disintegrate if a party breaches the conditions for one reason or another. Historians addressing the relation between the Mamluk Sultan Al-Zahir Baibars (ruled between 658 AH/ 1260 CE and 676 AH/ 1277 CE) and the Mongol Berke Khan noticed how this relation fluctuated between good and troubled at times. This fluctuation is maintained throughout the current research to reveal the historical truths regarding this relation. Many writers described this relation between Al-Zahir Baibars and the Mongol Berke Khan as good and unblemished overall, which was further strengthened when Berke Khan converted to Islam and waged many wars against his cousin Hulagu, especially in the year 653 AH (1255 CE), which was probably the most well-known war between the two. After Berhe Khan’s accession, Al-Zahir Baibars treated him according to Muslim codes of conduct with true support and friendliness to the extent of naming his eldest son Berke. This research will address the details of their relation, and how it was affected, positively or negatively. Moreover, the research will probe into Al-Zahir Baibars’ alliance with Berke Khan and others and the incidents that clearly displayed Baibars’ admiration for Berke Khan.